Use of educational internet-resources in the physical training course of the students engaged in taekwondo - Salamakha O.Y (Kharkov National Pedagogical University, 2010)
Informatization produces essential changes in the structure and organisation of the educative process, making it flexible, advancing and public. In order to optimaze the training process on taekwondo in conditions of the technical university the educational web-site, uniting texts, graphics, sound and video in one cover, has been created. Use of this internet-resource will generate interest in physical training, increase gnostic activity, stimulate the maximum rate of knowledge acquisition and ability development, solve a problem of health promotion.